Doxycycline Promotes Carcinogenesis & Metastasis via Chronic Inflammatory Pathway: An In Vivo Approach. - Neha Nanda; Devinder K Dhawan; Alka Bhatia; Akhtar Mahmood; Safrun Mahmood (PLoS ONE, 2016)
Background Doxycycline (DOX) exhibits anti-inflammatory, anti-tumor, and pro-apoptotic activity and is being tested in clinical trials as a chemotherapeutic agent for several cancers, including colon cancer. Materials & methods In the current study, the chemotherapeutic activity of doxycycline was tested in a rat model of colon carcinogenesis, induced by colon specific cancer promoter, 1,2, dimethylhydrazine (DMH) as well as study the effect of DOX-alone on a separate group of rats. Results Doxycycline administration in DMH-treated rats (DMH-DOX) unexpectedly increased tumor multiplicity, stimulated progression of colonic tumor growth from adenomas to carcinomas and revealed metastasis in small intestine as determined by macroscopic and histopathological analysis. DOX-alone treatment showed markedly enhanced chronic inflammation and reactive hyperplasia, which was dependent upon the dose of doxycycline administered. Moreover, immunohistochemical analysis revealed evidence of inflammation and anti-apoptotic action of DOX by deregulation of various biomarkers. Conclusion These results suggest that doxycycline caused chronic inflammation in colon, small intestine injury, enhanced the efficacy of DMH in tumor progression and provided a mechanistic link between doxycycline-induced chronic inflammation and tumorigenesis. Ongoing studies thus may need to focus on the molecular mechanisms of doxycycline action, which lead to its inflammatory and tumorigenic effects.